Implementation of the Project-Based Learning (PjBL) Model in Bioactivity Courses to Improve Students' Activities and Learning Outcomes - Indra Lasmana Tarigan; Madyawati Latief (Gema Wiralodra, 2022)
Bioactivity is an elective course at the Jambi University Chemistry Study Program which focuses on finding compounds that can act as drug candidates. This study aimed to determine the results of the implementation of the PjBL model in terms of the quality of the student activity process and the quality of the results, student achievement. This research is a descriptive study with the subject of semester V students for the 2021/2022 academic year who contracted the Bioactivity course. Data collection techniques were carried out by test and non-test techniques. The research data was measured and analyzed using the average percentage method on the results of the assessment of student activities (visual activities, oral activities, listening activities, writing activities, motor activities, mental activities, emotional activities) and student learning achievements (cognitive, affective, psychomotor) explained qualitatively and using data reduction, data display, and verification steps. The results showed that the implementation of the PjBL model improved the quality of the process, namely high student activity reaching 80% (2) the quality of the results in terms of: (a) cognitive learning achievement with an average of 75 known to be 46% - 88% of students completed. (b) affective learning achievement is known that 15% of students have very good affective learning achievement, 79% of students are good, 6% of students are poor, and 0% of students are very poor; (c) the quality of the results, namely psychomotor learning achievement on the project with an average of 87.5% very good; 10% is good, and 5% is not good